Faktor-Faktor yang Berpengaruh Terhadap Keinginan Migrasi Nasabah Bank Syariah di Semarang - Fauzi, Muchamad (STIE Widya Manggala, 2009)
A study of consumers’ intention to migrate from conventional bank to syariah bank has been examined in the early researches, but they show inconsistent result. Based on this inconsistency, this research tries to examine the influence of service quality, managerial performance, costumer satisfication and company’s reputation to the costumers’s intention to migrate from conventional to syariah bank in Semarang. Empirically, the research aims to obtain evidence of service quality, managerial performance, costumer satification and company’s reputation to the costumers’s intention to migrate. The population was all costumers of syariah bank in Semarang. The sampling technique was purposive sampling. The result show that service quality, managerial performance, costumer satification, and company’s reputation both partially and simultaneouslu have significant influence to the costumers’ intention to migrate from conventional bank to syariah bank proved by t value an F value.